Women and politics from the Perspectives of the Qur'an: A thematic tafsir study - Arrozaq, Muharris; Mauluddin, Arnanta; Fadhil, Muhammad (UIN Sunan Gunung Djati Bandung, 2025)
Islam is a religion which, in general understanding, is a universal religion. Islam is a teaching with broad dimensions, not just in one aspect, but covering several general aspects. Including the political aspect is an important part of Islam. In QS. Al-Taubah verse 7 contains a discussion of history and how, during the time of Rasulullah SAW, he solved a problem using politics. So that Islamic politics can regulate a good state and society. Apart from that, there is a discussion regarding the aspects of a leader who has good principles as a leader in the world of politics, contained in QS. Ali Imran verse 159, so that it can be a role model and guide in determining all decisions in politics. The position of women in the public sphere is also important in the world of politics, how a woman can become a leader but still maintain her dignity and position as a woman.